Student-Centered Insights into Remote Education: Needs, Challenges, and Adaptations - Consolacion, Roxan (Asia Research Network Journal of Education, 2025)
The Department of Technology Teacher Education implemented a new learning modality called Remote Teaching and Learning (RTL) during the pandemic. This study employed a mixed-methods research design to examine students' perceptions of their experiences with remote learning across seven key areas: learning modality, school health measures, academic needs, student engagement, relationships, cultural awareness, and school resource officers. A total of 197 students from various academic levels and specializations, ranging from freshmen to seniors, participated in the survey. Quantitative data were collected through structured questionnaires, which provided measurable insights into student experiences. For qualitative insights, open-ended questions were included in the survey, and responses were analyzed using thematic analysis to identify recurring patterns and emerging themes. This dual approach enabled a comprehensive understanding of students' remote learning experiences. Findings indicate a positive perception of remote learning, but challenges in technological proficiency, social interaction, and parental support persist. University safety protocols were effective, fostering a secure learning environment. Academic assistance remains a concern, requiring stronger support systems, leadership, and training. While students remain engaged, focus and attendance issues exist. Faculty observations highlight strong student-adult relationships and meaningful technology-based interactions. Effective communication between parents and faculty is crucial. Promoting cultural awareness requires leadership and professional development. Aligning with Sustainable Development Goals, this study advocates for a flexible, student-centered approach to post-pandemic education.